Efficacy of early stellar feedback in low gas surface density environments - Kannan, Rahul; Marinacci, Federico; Simpson, Christine M.; Glover, Simon; Hernquist, Lars (Monthly notices of the Royal Astronomical Society, 2020)
ABSTRACT. We present a suite of high-resolution radiation hydrodynamic simulations of a small patch (1 kpc2) of the interstellar medium (ISM) performed with ar